The methodology of Muhammad Asad in his tafsir - Mahmud, Maziah; Khan, Israr Ahmad; Samsudin, Sofiah (IIUM Press, International Islamic University Malaysia, 2017)
Muhammad Asad is a well-known scholar whose main contribution is in the field of tafsÊr. The Message of the Qur’Én represents his contribution towards that end. This book attempts to examine and explain all the components of the methodology applied by Muhammad Asad in his tafsÊr. These components as identified by the authors are: (1) The Qur’Én Interprets the Qur’Én, (2) Interpretation by Highly Authentic AÍÉdÊth, (3) Identification of the Central Theme of SËrah, (4) Condensation of the Contents of SËrah, (5) Utilization of Some Selected TafsÊr Works, (6) Deliberation over the Semantic Dimension of Words and Phrases, (7) Re-examination of the Value of the Reports on AsbÉb al-NuzËl, (8) Meccan and Medinan Revelations, and (9) Illustration from Judeo-Christian Sources